PREPARATION AND EVALUATION OF CLARITHROMYCIN LOADED BISMUTH SULFIDE (Bi2S3) NANOPARTICLES UTILIZING NANOTECHNOLOGY AS A NOVEL DRUG DELIVERY SYSTEM - from publication on author’s request, This article has been withdrawn (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
This article has been withdrawn from publication on author’s request